Human security - Pérez González, Carmen (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
The Human Development Report published by the UNDP in 1994 introduced the concept of human security. It was defined as safety from chronic threats, as hunger, illness of political repression, and protection from sudden hurtful disruptions in the patterns of daily life related to housing, work or to the community. This work aims to analyze the concept focusing, firstly, on its origins and, secondly, on the developments it has experimented. Besides that, some conclusions will be drown about the added value of this notion for Public International Law and for international relations.
Keywords: Human development; new dimensions of security; responsibility to protect; global public goods; International Human Rights Law; International Humanitarian Law